Comparative Analysis of the Financial Performance of Pt Manjadaduasatudua Indonesia Before the 2018-2019 Pandemic, the 2020-2021 Pandemic Period and After the 2022 Pandemic Economic Journal - Helena, Devy; Mulyani, Sri; Saepudin, Udin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
Financial performance is a description of the company's financial position analyzed by financial analysis tools, which can describe the company's performance achievements. This study aims to determine and compare the condition of financial performance at PT Manjadaduasatudua Indonesia before the 2018-2019 Pandemic, the 2020-2021 pandemic period and after the 2022 Pandemic. The analysis method used in this thesis research is a descriptive method which aims to analyze each data that has been processed and then draw conclusions. The type of research used is qualitative. The results showed that the financial performance of PT Manjadaduasatudua Indonesia before the 2018-2019 Pandemic under study had decreased, further decreased and was even declared FAILED when the 2020-2021 pandemic occurred, and the financial performance of PT Manjadaduasatudua Indonesia after the 2022 Pandemic tried to start over to improve the company in a better direction.